Il legamento artificiale: dal tutore intrarticolare al sostituto biomimetico - Manfreda, F.; Tei, M.; Placella, G.; Caraffa, A.; Cerulli, G. (Lo Scalpello - Journal, 2019)
THE ARTIFICIAL LIGAMENT: FROM INTRARTICULAR BRACE TO BIOMIMETIC SUBSTITUTE In ACL reconstruction, the search for the ideal transplant still finds too many controversies. The choice of surgeons has always turned towards the biological solution. The history of artificial ligaments has shown continuous failures. LARS is the most successful synthetic graft in recent years but it should be considered as an “intra-articular brace” and should be reserved only to specific indications. Currently, the research is focusing on the “bioactive” ligament: new treatments of terephthalate, in fact, could make these ligaments able to become future biological-like ligaments, overcoming all the limitations of artificial graft.